Предмет: Математика,
автор: Dren
(1,1x - 0,21c) + (2,2x - 4b) - (3,3x - 4b) =
(2,31x - 2,37c) - (2,47x - 0,33c) - (2,4c - 0,16x) =
- (0,1a + 1,1b) - (0,7b - 1,05a) - (1,1b + 0,95a) =
(a + c) • ( - 2,1) - (5,3a - 2,1c) =
2,06 • (x - c) + (1,03x - 2,51c) • (- 2) =
Ответы
Автор ответа:
0
1,1x-0,21c+2,2x-4b-3,3x+4b=0,21c
2,31x-2,37c-2,47x+0,33c-2,4c+0,16x=-2,44c
-0,1a-1,1b-0,7b+1,05a-1,1b-0,95a=-2,9b
Автор ответа:
0
2,06*(x-c)+(1,03-2,51c)*(-2)=296
Похожие вопросы
Предмет: Українська мова,
автор: dfjffjxjj
Предмет: Қазақ тiлi,
автор: grishalanin1982
Предмет: Русский язык,
автор: anel64582
Предмет: Математика,
автор: ekz